Photobiomodulation in orofacial harmonization practice: A narrative literature review (Research, Society and Development, 2025)
The present study aims to evaluate, through a narrative literature review, the status quo of the use of photobiomodulation in facial rejuvenation within the clinical practice of Orofacial Harmonization. Based on the application of non-ionizing light, such as lasers and LEDs at different wavelengths, this approach promotes the absorption of light energy by chromophores present in mitochondria, resulting in increased adenosine triphosphate (ATP) production and activation of biochemical processes that favor skin repair and revitalization. Skin aging, resulting from intrinsic factors such as hormonal changes and genetic predisposition, and extrinsic factors, particularly exposure to ultraviolet radiation, leads to collagen degradation, loss of elasticity, and wrinkle formation, compromising the structural and aesthetic integrity of the face. Photobiomodulation works to reverse, or at least mitigate, these effects through the stimulation of collagen and elastin synthesis, reduction of inflammation, and improvement of blood and lymphatic circulation. Different wavelengths present specific effects. Combining photobiomodulation with other techniques, such as microneedling, chemical peels, and the use of dermocosmetics, enhances clinical outcomes by accelerating cell renewal and promoting firmer, hydrated skin with improved texture. In addition to the physiological benefits, these procedures positively impact patients' self-esteem and psychosocial well-being, emphasizing the importance of an integrated approach in clinical practice. Thus, the technique significantly contributes to the advancement of aesthetic treatments, combining technology and scientific knowledge to provide visible and long-lasting results.